PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PERUSAHAAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - welly, welly; Dewi, Citra; Djuniar, Lis; Zuraidah, Ida; Sabrina, Nina (Universitas Muhammadiyah Palembang, 2023)
The aim of the research is to determine the influence of the quality of accounting information systems and internal control systems on company performance both partially and simultaneously, to determine the influence of the quality of accounting information systems and internal control systems on company performance with organizational culture as a moderating variable. This type of research is associative research, primary data, 45 research samples consisting of employees from the finance department and internal supervision units at BUMD. Questionnaire and interview collection methods. The analysis method is quantitative analysis. The results of this research show that the quality of the accounting information system and the internal control system simultaneously influence company performance. Partially, the quality of the accounting information system and internal control system influences company performance. In moderation, the quality of the accounting information system has no effect on company performance, moderated by organizational culture and the same goes for the internal control system.